Innovation Motives in Family Firms: A Transgenerational View. (March 2020) - Diaz-Moriana, Vanessa; Clinton, Eric; Kammerlander, Nadine; Lumpkin, G. T.; Craig, Justin B.
Drawing on the transgenerational entrepreneurship perspective, we employ a multiple case study approach to investigate why multigenerational family firms innovate. The data collection process drew upon five in-depth cases comprising 42 semistructured interviews, 25 participant observations, and several thousand pages of historical data dating from 1916 to 2017. We find patterns on how the firms' long-term view—embracing both the past and the future—influences the innovation motives of these firms. Specifically, we identify three innovation patterns: conserving, persisting and legacy-building . We introduce a set of propositions and a framework linking long-term orientation dimensions to innovation motives and innovation outcomes. Our research thus contributes to a more fine-grained understanding of innovation behavior in family firms.